An economic evaluation: Simulation of the cost‐effectiveness and cost‐utility of universal prevention strategies against osteoporosis‐related fractures. (15th January 2013) - Nshimyumukiza, Léon; Durand, Audrey; Gagnon, Mathieu; Douville, Xavier; Morin, Suzanne; Lindsay, Carmen; Duplantie, Julie; Gagné, Christian; Jean, Sonia; Giguère, Yves; Dodin, Sylvie; Rousseau, François; et al.
Abstract: A patient‐level Markov decision model was used to simulate a virtual cohort of 500, 000 women 40 years old and over, in relation to osteoporosis‐related hip, clinical vertebral, and wrist bone fractures events. Sixteen different screening options of three main scenario groups were compared: (1) the status quo (no specific national prevention program); (2) a universal primary prevention program; and (3) a universal screening and treatment program based on the 10‐year absolute risk of fracture. The outcomes measured were total directs costs from the perspective of the public health care system, number of fractures, and quality‐adjusted life‐years (QALYs). Results show that an option consisting of a program promoting physical activity and treatment if a fracture occurs is the most cost‐effective (CE) (cost/fracture averted) alternative and also the only cost saving one, especially for women 40 to 64 years old. In women who are 65 years and over, bone mineral density (BMD)‐based screening and treatment based on the 10‐year absolute fracture risk calculated using a Canadian Association of Radiologists and Osteoporosis Canada (CAROC) tool is the best next alternative. In terms of cost‐utility (CU), results were similar. For women less than 65 years old, a program promoting physical activity emerged as cost‐saving but BMD‐based screening with pharmacological treatment also emerged as an interesting alternative. In conclusion, a program promoting physical activity is the most CE and CU option for women 40 to 64 years old. BMD screening and pharmacological treatment might be considered a reasonable alternative for women 65 years old and over because at a healthcare capacity of $50, 000 Canadian dollars ($CAD) for each additional fracture averted or for one QALY gained its probabilities of cost‐effectiveness compared to the program promoting physical activity are 63% and 75%, respectively, which could be considered socially acceptable. Consideration of the indirect costs could change these findings. © 2013 American Society for Bone and Mineral Research